Evaluasi Potensi Kombinasi Buah dan Daun Mangrove sebagai Pakan Alternatif Ruminansia: Pendekatan In-Vitro - Yanti, Gusri; Elmiati, Reni; Anggraini, Okta Refi; Triani, Hera Dwi (Universitas Bengkulu, 2024)
This study aimed to determine the optimal combination of mangrove leaves (Rhizophora apiculata) and pidada fruit (Sonneratia alba) to improve nutrient digestibility as ruminant feed through in-vitro methods. The experiment used a Completely Randomized Design (CRD) with four treatments: P0: Mangrove leaves (100%); P1: Pidada fruit (100%); P2: Mangrove leaves (50%) + Pidada fruit (50%); P3: Mangrove leaves (75%) + Pidada fruit (25%), with each treatment replicated four times. Nutrient digestibility was assessed using the Tilley and Terry method. The results showed that treatment P3 (the combination of 75% mangrove leaves and 25% pidada fruit) achieved dry matter digestibility of 59.38% and organic matter digestibility of 62.56%, with a total volatile fatty acid (VFA) concentration of 125.54 mM and ammonia (NH3) concentration of 16.76 mg/100 ml. This combination exhibited high digestibility, indicating its potential as an alternative ruminant feed.